2022
DOI: 10.1177/02676583221099237
|View full text |Cite
|
Sign up to set email alerts
|

The acquisition of L2 allophonic variants: The role of phonological distribution and lexical cues

Abstract: Adult learners acquire second language (L2) allophones with experience. We examine two mechanisms which may support the acquisition of allophonic variants in second language acquisition. One of the mechanisms is based on the distribution of phones with respect to their phonological context (i.e. phonological distribution). The other is based on the role the phones play in contrasting words (i.e. lexical contrast). Experiment 1 established adult native English speakers’ baseline sensitivity to the novel [b]–[β]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 56 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…Existing studies have shown that adults typically experience more difficulty in perceiving acoustic differences in novel, non-native, phoneme contrasts as compared to children and infants (e.g., Best & Strange, 1992), and are generally poorer at extracting distributional cues from training stimuli (e.g., Wanrooij et al, 2014). This is likely related to the manner in which language learning strategies shift from distributional learning with age, with adults typically favouring the use of more salient acoustic and lexical cues for the acquisition of novel speech sound contrasts (Barrios et al, 2022;Hayes-Harb, 2007;Liu, et al 2022;Werker, 2018). As the study we adapted was originally conducted on Grade 3 Dutch children (Vandermosten et al, 2018), children in the original study were likely more sensitive to the differences in dental-retroflex ambiguity in the stimuli, and would have been more adept at extracting distributional cues from the training set in a much shorter period of time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing studies have shown that adults typically experience more difficulty in perceiving acoustic differences in novel, non-native, phoneme contrasts as compared to children and infants (e.g., Best & Strange, 1992), and are generally poorer at extracting distributional cues from training stimuli (e.g., Wanrooij et al, 2014). This is likely related to the manner in which language learning strategies shift from distributional learning with age, with adults typically favouring the use of more salient acoustic and lexical cues for the acquisition of novel speech sound contrasts (Barrios et al, 2022;Hayes-Harb, 2007;Liu, et al 2022;Werker, 2018). As the study we adapted was originally conducted on Grade 3 Dutch children (Vandermosten et al, 2018), children in the original study were likely more sensitive to the differences in dental-retroflex ambiguity in the stimuli, and would have been more adept at extracting distributional cues from the training set in a much shorter period of time.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of Escudero and colleagues, the participants had already begun learning Dutch or were living in the Netherlands, and would therefore have had relevant prior exposure to the Dutch /ɑ/-/aː/ vowel contrast that they were trained on in the studies (Escudero et al, 2011;Escudero and Williams, 2014;Wanrooij et al, 2013). On the other hand, adults who were trained on completely novel speech sounds which did not have any structural overlaps with the languages in their repertoires appear to have been unable to utilise distributional cues for learning, instead focusing on more salient cues at hand such as acoustic cues (e.g., Liu et al 2022), andlexical cues (Hayes-Harb, 2007;Barrios et al, 2022).…”
Section: Distributional Learning Later In Lifementioning
confidence: 99%